PELATIHAN PEMANFAATAN SUMBER PUSTAKA DALAM MENUNJANG PENULISAN MAKALAH ILMIAH BAGI GURU SMK NEGERI 10 TANGERANG - Merry Lapasau; Mamik Suendarti; Lestarini Sumotenodjo (LP4MK STKIP PGRI Lubuklinggau, 2020)
Utilization of digital library resources in supporting the writing of scientific papers among teachers of SMK 10 Tangerang is still not practiced. Based on the results of the initial questionnaire, it was found out that the vocational high school teachers did not know much about how to find or utilize electronic library resources to support writing scientific papers. Therefore, this community service activity by UNINDRA aims to improve the knowledge and abilities of teachers in searching, utilizing, and compiling library resources in online databases systematically so that they are able to apply this knowledge in writing scientific papers for publication in journals. The method used is the lecture and question and answer method. It can be concluded that the PKM activities in SMKN 10 Tangerang in providing guidance on writing scientific papers, especially regarding the use of library resources, can be well received and followed by the teachers. For further activities, further complete trainings are needed in the form of writing scientific articles so that teachers are able to write papers for national journals independently with maximum utilization of library resources.